The regulatory action of acetylcholine and its receptors on B4 and C4 leukotriene formation in the porcine endometrium after experimental inflammogenic Escherichia coli infection - Jana Barbara; Całka Jarosław; Bulc Michał; Kawka Dominika (Journal of Veterinary Research)
Endometritis is a very common pathology in animals which changes endometrial leukotriene (LT) formation and muscarinic 2 and 3 receptor subtypes (M2R/M3R) and α-7 nicotinic acetylcholine (ACh) receptor (α-7 nAChR) expression patterns. With the relationship between ACh, its receptors and LT production remaining unclear, the role of M2R, M3R and α-7 nAChR in action of ACh on the 5-lipoxygenase (5-LO), LTA4 hydrolase (LTAH) and LTC4 synthase (LTCS) protein abundances in the inflamed porcine endometrium and on the tissue secretion of LTB4 and LTC4 were studied.